Ecopedagogy of Island Communities: Conception, Planning to Action in Building Environmental Awareness in Kelapa Island and Harapan Island, Administrative District Kepulauan Seribu-DKI Jakarta - .Tarmiji Alkhudri, Ahmad; ., Suyuti; Heryanto, Nano; Gustiannisa, Saskia; Puji Hanifah, dan (KnE Social Sciences, 2024)
This study intends to examine the conception, planning, and action in building environmental awareness in Kelapa Island and Harapan Island, Administrative District Kepulauan Seribu, DKI Jakarta. Methodologically, this study is based on a critical paradigm and a qualitative approach. The study was conducted in May–June 2023. Data collection techniques were observation and in-depth interviews. Whereas, the data analysis technique was interpretive phenomenological analysis. The study results show that: (i) education is the main focus of building environmental awareness; (ii) environmental awareness has been instilled in children from an early age through informal, formal, and non-formal education. In the context of informal and non-formal education, parents play an active role in instilling environmental awareness values. Furthermore, in formal education planting environmental awareness is socialized through the learning curriculum; (iii) conception and planning of environmental awareness in the community is carried out continuously and sustainably; and (iv) concrete actions to build community environmental awareness are carried out with various campaigns, movements and routine actions carried out by multi-stakeholders to create environmental sustainability on the Kelapa Island and Harapan Island, Administrative District Kepulauan Seribu-DKI Jakarta. Keywords: ecopedagogy, environmental conception and action, Thousand Islands